An In 3+ and F - Co-doped TiO2 giant dielectric ceramic material and preparation method
Patent Information
- Application Number
- CN202411747275.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-12-02
AI Technical Summary
当大量氧空位产生,会导致缺陷簇的解缔,也会导致传导损耗,进而不可避免地使介电损耗增大
本发明打破传统施、受主离子共掺杂TiO2体系的策略,仅选用一种原料InF3实现在TiO2体系的Ti位和O位同时进行掺杂取代,其中,In3+作为受主掺杂产生氧空位;F取代O位提供电子,且大电负性的F
局域电子,利于Ti4++ e
Ti3+,提高半导性,同时还可以调节氧空位浓度;制备的In3+和F
共掺杂TiO2巨介电陶瓷材料具有高的介电常数和低的介电损耗、良好的频率和温度稳定性,In0.05Ti0.925O1.85F0.15巨介电陶瓷介电常数高达33429,损耗低至0.06,温度稳定性达到X9R;
Smart Images

Figure CN119613102B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials technology, and relates to giant dielectric ceramic materials and their preparation methods, specifically involving an In... 3+ and F Co-doped TiO2 giant dielectric ceramic materials and their preparation methods. Background Technology
[0002] In recent years, TiO2-based giant dielectric ceramics have become a research hotspot as a novel dielectric material for multilayer ceramic capacitors (MLCCs), and have become candidate materials for the development and design of next-generation high-end weaponry and integrated circuits. Reference 1 (WB Hu et al, Nature Mater., 12(2013)821.) first reported the application of TiO2-based giant dielectric ceramics. 5+ ), receiver (In 3+ Co-doped TiO2 ceramics yield high dielectric constants (greater than 10). 4 TiO2-based materials exhibit high dielectric properties, low dielectric loss (less than 0.05%), and good frequency and temperature stability. Recent research has focused on achieving giant dielectric properties in TiO2-based materials through donor and acceptor ion co-doping strategies. For example, reference 2 (Y. Xue et al, Ceram. Int., 50(2024) 51848-51857.) reports different donor doping (V0...)... 5+ 、Nb 5+ and Ta 5+ ) and recipient (In 3+ Co-doped TiO2 ceramics; references 3 (XB Zhou et al, Ceram. Int., 46(2020) 11921-11925.), 4 (J. Liu et al, Ceram. Int., 46(2020) 12059-12066.), and 5 (BC Guo et al, Ferroelectrics., 589(2022) 35-44.) report different acceptor ion doping (e.g., Ag). + Ca 2+ 、Sr 2+ Ba 2+ 、Nd 3+ 、Sm 3+ La 3+ and Gd 3+ ) and benefactors (Nb 5+ and Ta 5+Giant dielectric properties were obtained in co-doped TiO2 ceramics. Donor ion doping substituted Ti sites to generate electrons, while acceptor ion doping generated oxygen vacancies. Researchers attributed the giant dielectric mechanism primarily to effects such as electron pinned defect dipoles (EPDD), internal barrier layer capacitance (IBLC), and surface barrier layer capacitance (SBLC). Among these, electrons provided by the donor dopant in the triangular (… ) or rhombus ( (A=Ti 4+ / In 3+ / Ti 3+ Localization is achieved in defect clusters. Oxygen vacancies induced by host ion doping are key to the formation of defect dipole clusters. In the IBLC polarization mechanism, electronic hopping polarization occurs as follows: Oxygen vacancies induce semiconducting properties in the grains, resulting in a high dielectric constant. In the two dominant dielectric mechanisms (EPDD and IBLC), oxygen vacancies form defect dipole clusters in the former, while in the latter, interfacial polarization occurs at grain boundaries, with electrons existing in a localized or long-range hopping conduction manner. The generation of a large number of oxygen vacancies leads to the disintegration of defect clusters, resulting in conduction losses and inevitably increasing dielectric losses. Therefore, developing a novel ion doping method to reduce the oxygen vacancy concentration in TiO2 materials and breaking away from the traditional donor doping strategy of providing electrons is crucial for improving the dielectric properties of current conventional donor-acceptor co-doped TiO2 giant dielectric materials. Summary of the Invention
[0003] To address the shortcomings of existing technologies, the present invention aims to provide an In material with high dielectric constant, low dielectric loss, and good frequency and temperature stability. 3+ and F Co-doped TiO2 giant dielectric ceramic materials and their preparation methods are presented, featuring single raw materials, simple preparation process, good reproducibility, and low cost.
[0004] To achieve the above objectives, the present invention employs the following technical solution: A kind of In 3+ and F Co-doped TiO2 giant dielectric ceramic materials, with the general structural formula In x Ti 1-3x / 2 O 2-3x F 3x , where x takes values from 0.03 to 0.06.
[0005] Preferably, the general structural formula is In x Ti 1-3x / 2 O 2-3x F 3x , where x = 0.05.
[0006] This invention protects an In as described above 3+ and F The preparation method of co-doped TiO2 giant dielectric ceramic material includes the following steps: Step 1: Weigh InF3 and TiO2 powder raw materials according to the stoichiometric ratio, put the weighed raw materials into a ball mill jar for ball milling and drying, and then grind and sieve to obtain a raw material mixture; Step 2: Place the raw material mixture into an alumina crucible, then place the crucible in a box furnace, and pre-calcine it at 1050~1250 ºC for 1~4 hours under an air atmosphere. After ball milling and drying, grind and sieve to obtain pre-calcined powder. Step 3: After pressing the pre-fired powder into sheets, place them in a tube furnace and heat them from room temperature to 1220~1400ºC under a nitrogen atmosphere for 3~8 hours. Finally, allow them to cool naturally to room temperature to obtain ceramic materials with high dielectric constant, low dielectric loss and good temperature stability.
[0007] Preferably, the ball milling in steps one and two involves using zirconia balls as the milling balls and deionized water as the milling medium, and then fully mixing and milling for 6 to 8 hours.
[0008] Preferably, the drying process described in steps one and two involves placing the item in an oven and drying it at 80-100 ºC for 24 hours.
[0009] Preferably, the grinding in step two involves grinding again in a mortar and pestle for 30 to 60 minutes.
[0010] Preferably, the sieving in step two is sieve sieve 120~200 mesh.
[0011] Preferably, the pre-calcined powder tablets mentioned in step three are pre-pressed into cylindrical blanks with a diameter of 8 mm using a mold, and then cold isostatically pressed for 3-5 minutes at a pressure of 200 MPa in a cold isostatic press.
[0012] Compared with the prior art, the present invention has the following technical effects: This invention breaks with the traditional strategy of co-doping TiO2 systems with donor and acceptor host ions, and instead uses only one raw material, InF3, to achieve simultaneous doping substitution at both Ti and O sites in the TiO2 system. Specifically, In... 3+ As an acceptor doper, oxygen vacancies are generated; F Replacing the O-position to provide electrons, and the highly electronegative F Localized electronics, beneficial to Ti 4+ + e Ti 3+ This improves semiconductivity and also allows for adjustment of oxygen vacancy concentration; the prepared In 3+ and F Co-doped TiO2 giant dielectric ceramics possess high dielectric constants, low dielectric losses, and good frequency and temperature stability. 0.05 Ti 0.925 O 1.85 F 0.15 The giant dielectric ceramic has a dielectric constant of up to 33429, a loss as low as 0.06, and temperature stability reaching X9R. This invention uses a single raw material, has a simple preparation process, good repeatability, low cost, and high yield. Attached Figure Description
[0013] Figure 1 In prepared in Examples 1 to 4 3+ and F XRD patterns of co-doped TiO2 giant dielectric ceramic materials; Figure 2 In prepared in Examples 1 to 4 3+ and F Curves showing the changes in dielectric constant and dielectric loss of co-doped TiO2 giant dielectric ceramic materials with frequency at 1 kHz room temperature; Figure 3 The temperature stability spectra of the InF3-doped TiO2 giant dielectric ceramic materials prepared in Examples 1 to 4 are shown at 1 kHz. Detailed Implementation
[0014] The specific content of the present invention will be further explained in detail below with reference to the embodiments.
[0015] Example 1 Step 1: Follow In 0.05 Ti 0.925 O 1.85 F 0.15 According to the stoichiometric ratio, 2.0836 g of InF3 with a purity of 99.99% and 17.9184 g of TiO2 with a purity of 99.99% were weighed and placed in a nylon can. Using zirconium balls as grinding balls and deionized water as the grinding medium, the mixture was ball-milled for 6 hours at a speed of 400 rpm. After drying at 80 ℃ for 24 hours, the mixture was ground in a mortar for 30 minutes and passed through a 120-mesh sieve to obtain the raw material mixture. Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, and then place the crucible in a box furnace. Under an air atmosphere, heat it from room temperature to 1150 ℃ at a heating rate of 5 ℃ / min, hold it at that temperature for 2 hours, and let it cool naturally to room temperature with the furnace. Remove it from the furnace, ball mill it for 6 hours using a ball mill at a speed of 400 rpm, dry it in a drying oven at 80 ℃ for 24 hours, grind it again in a mortar for 30 minutes, and pass it through a 120-mesh sieve to obtain pre-calcined powder. Step 3: Place the pre-calcined powder into a stainless steel mold with a diameter of 8 mm, and press it into a cylindrical blank using a powder press without applying pressure. Place the cylindrical blank in a cold isostatic press and cold isostatically press it for 3 minutes at a pressure of 200 MPa. Place the cylindrical blank on a zirconia plate, and place the zirconia plate in a tube furnace. Introduce a nitrogen atmosphere and heat the furnace to 1370 ℃ at a heating rate of 5 ℃ / min / min. Hold the temperature for 4 hours, and allow it to cool naturally to room temperature in the furnace to obtain In. 3+ and F Co-doped TiO2 giant dielectric ceramic material.
[0016] Example 2 Step 1: Follow In 0.03 Ti 0.955 O 1.91 F 0.09 According to the stoichiometric ratio, 1.2662 g of InF3 with a purity of 99.99% and 18.7359 g of TiO2 with a purity of 99.99% were weighed and placed in a nylon can. Using zirconium balls as grinding balls and deionized water as the grinding medium, the mixture was ball-milled for 7 hours at a speed of 400 rpm. After drying at 90 ℃ for 24 hours, the mixture was ground in a mortar for 50 minutes and passed through a 150-mesh sieve to obtain the raw material mixture. Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, and then place the crucible in a box furnace. Under an air atmosphere, heat it from room temperature to 1050 ℃ at a heating rate of 5 ℃ / min, hold it at that temperature for 4 hours, and let it cool naturally to room temperature with the furnace. Remove it from the furnace, ball mill it for 7 hours using a ball mill at a speed of 400 rpm, dry it in a drying oven at 90 ℃ for 24 hours, grind it again in a mortar for 50 minutes, and pass it through a 150-mesh sieve to obtain pre-calcined powder. Step 3: Place the pre-calcined powder into a stainless steel mold with a diameter of 8 mm, and press it into a cylindrical blank using a powder press without applying pressure. Place the cylindrical blank in a cold isostatic press and cold isostatically press it for 4 minutes at a pressure of 200 MPa. Place the cylindrical blank on a zirconia plate, and place the zirconia plate in a tube furnace. Introduce a nitrogen atmosphere and heat the furnace to 1220 ℃ at a heating rate of 5 ℃ / min / min. Hold the temperature for 8 hours, and allow it to cool naturally to room temperature in the furnace to obtain In. 3+ and F Co-doped TiO2 giant dielectric ceramic material.
[0017] Example 3 Step 1: Follow In 0.04 Ti 0.94 O 1.88 F 0.12According to the stoichiometric ratio, 1.6775 g of InF3 with a purity of 99.99% and 18.3241 g of TiO2 with a purity of 99.99% were weighed and placed in a nylon can. Using zirconium balls as grinding balls and deionized water as the grinding medium, the mixture was ball-milled for 8 hours at a speed of 400 rpm. After drying at 100 ℃ for 24 hours, the mixture was ground in a mortar for 60 minutes and passed through a 200-mesh sieve to obtain the raw material mixture. Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, and then place the crucible in a box furnace. Under an air atmosphere, heat it from room temperature to 1250 ℃ at a heating rate of 5 ℃ / min, hold it at that temperature for 1 hour, and let it cool naturally to room temperature with the furnace. Remove it from the furnace, ball mill it for 8 hours using a ball mill at a speed of 400 rpm, dry it in a drying oven at 100 ℃ for 24 hours, grind it again in a mortar for 60 minutes, and pass it through a 200-mesh sieve to obtain pre-calcined powder. Step 3: Place the pre-calcined powder into a stainless steel mold with a diameter of 8 mm, and press it into a cylindrical blank using a powder press without applying pressure. Place the cylindrical blank in a cold isostatic press and cold isostatically press it for 5 minutes at a pressure of 200 MPa. Place the cylindrical blank on a zirconia plate, and place the zirconia plate in a tube furnace. Introduce a nitrogen atmosphere and heat the furnace to 1400 ℃ at a heating rate of 5 ℃ / min / min. Hold the temperature for 3 hours, and allow it to cool naturally to room temperature in the furnace to obtain In. 3+ and F Co-doped TiO2 giant dielectric ceramic material.
[0018] Example 4 Step 1: Follow In 0.06 Ti 0.91 O 1.82 F 0.18 According to the stoichiometric ratio, 2.4847 g of InF3 with a purity of 99.99% and 17.5175 g of TiO2 with a purity of 99.99% were weighed and placed in a nylon can. Using zirconium balls as grinding balls and deionized water as the grinding medium, the mixture was ball-milled for 6 hours at a speed of 400 rpm. After drying at 80 ℃ for 24 hours, it was ground in a mortar for 30 minutes and passed through a 120-mesh sieve to obtain the raw material mixture. Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, and then place the crucible in a box furnace. Under an air atmosphere, heat it from room temperature to 1150 ℃ at a heating rate of 5 ℃ / min, hold it at that temperature for 2 hours, and let it cool naturally to room temperature with the furnace. Remove it from the furnace, ball mill it for 6 hours using a ball mill at a speed of 400 rpm, dry it in a drying oven at 80 ℃ for 24 hours, grind it again in a mortar for 30 minutes, and pass it through a 120-mesh sieve to obtain pre-calcined powder. Step 3: Place the pre-calcined powder into a stainless steel mold with a diameter of 8 mm, and press it into a cylindrical blank using a powder press without applying pressure. Place the cylindrical blank in a cold isostatic press and cold isostatically press it for 3 minutes at a pressure of 200 MPa. Place the cylindrical blank on a zirconia plate, and place the zirconia plate in a tube furnace. Introduce a nitrogen atmosphere and heat the furnace to 1370 ℃ at a heating rate of 5 ℃ / min / min. Hold the temperature for 4 hours, and allow it to cool naturally to room temperature in the furnace to obtain In. 3+ and F Co-doped TiO2 giant dielectric ceramic material.
[0019] Figure 1 In prepared in Examples 1-4 3+ and F The XRD patterns of the co-doped TiO2 giant dielectric ceramic materials show that all samples obtained a pure rutile TiO2 phase structure with no second phase. All dopants entered the TiO2 lattice, indicating that pure rutile TiO2 ceramic samples were prepared in Examples 1-4.
[0020] Figure 2 In prepared in Examples 1-4 3+ and F The dielectric constant and dielectric loss of co-doped TiO2 giant dielectric ceramic materials as a function of frequency at 1 kHz room temperature are shown in the curves. Figure 2 Giant dielectric properties can be obtained for all samples. When x When the dielectric constant is 0.05, its dielectric constant is as high as 33429, and the loss is only 0.06.
[0021] Figure 3 This refers to the temperature stability of the InF3-doped TiO2 giant dielectric ceramic materials prepared in Examples 1-4 at 1 kHz. When... x When = 0.05, X9R (Δε) is satisfied. r / ε 25 ºC : 55 ºC - 200 ºC Practical applications of ± 15%).
[0022] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; any deductions or substitutions made by those skilled in the art without departing from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A kind of In 3+ and F - Co-doped TiO2 giant dielectric ceramic material, characterized in that, The general structural formula is In x Ti 1-3x / 2 O 2- 3x F 3x , where x takes values from 0.03 to 0.
06.
2. The In as described in claim 1 3+ and F - Co-doped TiO2 giant dielectric ceramic material, characterized in that, The general structural formula is In x Ti 1-3x / 2 O 2-3x F 3x , where x = 0.
05.
3. An In as described in claim 1 or 2 3+ and F - The method for preparing co-doped TiO2 giant dielectric ceramic materials is characterized by, Includes the following steps: Step 1: Weigh InF3 and TiO2 powder raw materials according to the stoichiometric ratio, put the weighed raw materials into a ball mill jar for ball milling and drying, and then grind and sieve to obtain a raw material mixture; Step 2: Place the raw material mixture into an alumina crucible, then place the crucible in a box furnace, and pre-calcine it at 1050-1250°C for 1-4 hours under an air atmosphere. After ball milling and drying, grind and sieve to obtain pre-calcined powder. Step 3: After pressing the pre-fired powder into sheets, place them in a tube furnace and heat them from room temperature to 1220-1400℃ under a nitrogen atmosphere for 3-8 hours. Finally, allow them to cool naturally to room temperature to obtain ceramic materials with high dielectric constant, low dielectric loss and good temperature stability.
4. The In as described in claim 3 3+ and F - The method for preparing co-doped TiO2 giant dielectric ceramic materials is characterized by, The ball milling described in steps one and two involves using zirconia balls as the milling balls and deionized water as the milling medium, and then fully mixing and milling for 6 to 8 hours.
5. The In as described in claim 3 3+ and F - The method for preparing co-doped TiO2 giant dielectric ceramic materials is characterized by, The drying process described in steps one and two involves placing the item in an oven and drying it at 80–100°C for 24 hours.
6. The In as described in claim 3 3+ and F - The method for preparing co-doped TiO2 giant dielectric ceramic materials is characterized by, The grinding described in step two involves grinding again in a mortar and pestle for 30 to 60 minutes.
7. The In as described in claim 3 3+ and F - The method for preparing co-doped TiO2 giant dielectric ceramic materials is characterized by, The sieving mentioned in step two refers to passing the material through a 120-200 mesh sieve.
8. The In as described in claim 3 3+ and F - The method for preparing co-doped TiO2 giant dielectric ceramic materials is characterized by, The pre-fired powder tablets mentioned in step three are pre-pressed into cylindrical blanks with a diameter of 8mm using a mold, and then cold isostatically pressed for 3-5 minutes at a pressure of 200MPa in a cold isostatic press.
Citation Information
Patent Citations
In + Ta co-doped TiO2-based giant dielectric ceramic as well as preparation method and application thereof
CN114262223A
Al / Ga / In + Ta co-doped TiO2-based giant dielectric ceramic as well as preparation method and application thereof
CN114773053A